Persaingan, legitimasi kekuasaan, dan marketing politik : pembelajaran politik Pemilu 2009 - Firmanzah (Jakarta : Yayasan Obor Indonesia, 2010)
Political campaign and competition of participants in General elections 2009 in Indonesia.
Includes bibliographical references (p. 591-609) dan index.
Keywords: Political parties -- Indonesia; Indonesia -- Politics and government